(untitled) (GAIMS Journal of Medical Sciences, 2025)
Objective India is witnessing a demographic transition with the elderly population (≥ 60 years) projected to rise to 19% by 2050. This shift is associated with increased multimorbidity and a dual burden of communicable and non-communicable diseases, posing significant public health challenges. In this context, the present study aimed to assess the prevalence and pattern of self-reported morbidities among the elderly, identify common health conditions, and examine their association with socio-demographic factors in the field practice area of B.J. Medical College, Ahmedabad. Materials and Methods A cross-sectional study was carried out from August 2021 to August 2022 among 700 elderly individuals (≥60 years) attending health camps in five urban field practice areas. Data were collected using a pre-tested structured proforma through personal interviews, including socio-demographic profile, morbidity history, and age-related health conditions. Anthropometric measurements were also taken. Analysis was performed using descriptive statistics, chi-square test, Fisher’s exact test, and z-test, with significance set at p < 0.05. Results Of the 700 participants (mean age 72.1±5.4 years), 70.7% reported at least one morbidity. Hypertension (53.4%) and diabetes (25.1%) were the leading chronic conditions, while visual problems (62.4%), oral issues (45.0%), and joint pain (38.7%) were the most frequent age-related conditions. Females had significantly higher prevalence of hypertension (60.4%) and visual problems, whereas males had higher ischemic heart disease (6.1%) and asthma (10.2%). The 60-79 year age-group had more hypertension (55.5%) and diabetes (42.3%), while those ≥80 years had higher ischemic heart disease (10.7%) and cancer (6.5%). Morbidity was significantly associated with age, sex, type of family, occupation, and BMI. Conclusions A substantial burden of chronic and age-related conditions was observed among the elderly, with clear socio-demographic variations. Females and the oldest-old were especially vulnerable. Strengthening community-based screening, promoting lifestyle modification, and providing gender- and age-sensitive interventions are essential for improving geriatric health outcomes.